Relativity made relatively easy - Steane, Andrew M. (Oxford, United Kingdom : Oxford University Press, 2012)
Relativity Made Relatively Easy presents an extensive study of Special Relativity and a gentle (but exact) introduction to General Relativity for undergraduate students of physics. Assuming almost no prior knowledge, it allows the student to handle all the Relativity needed for a university course, with explanations as simple, thorough, and engaging as possible.
The aim is to make manageable what would otherwise be regarded as hard; to make derivations as simple as possible and physical ideas as transparent as possible. Lorentz invariants and four-vectors are introduced early on, but tensor notation is postponed until needed. In addition to the more basic ideas such as Doppler effect and collisions, the text introduces more advanced material such as radiation from accelerating charges, Lagrangian methods, the stress-energy tensor, and introductory General Relativity, including Gaussian curvature, the Schwarzschild solution, gravitational lensing, and black holes. A second volume will extend the treatment of General Relativity somewhat more thoroughly, and also introduce Cosmology, spinors, and some field theory.
Appendices. Some basic arguments -- Constants and length scales -- Derivatives and index notation -- The field of an arbitrarily moving charge.
Includes bibliographical references (p. [413]) and index
Keywords: Special relativity (Physics); Relativity (Physics)